The REstart or STop Antithrombotics Randomised Trial (RESTART) after stroke due to intracerebral haemorrhage: study protocol for a randomised controlled trial - Al-Shahi Salman, Rustam; Dennis, Martin S.; Murray, Gordon D.; Innes, Karen; Drever, Jonathan; Dinsmore, Lynn; Williams, Carol; White, Philip M.; Whiteley, William N.; Sandercock, Peter A.G.; Sudlow, Cathie L.M.; Newby, David E.; et al. (BioMed Central, 2018)
Background